What Impairs Balance in Ankylosing Spondylitis? Posture or Disease Activity? - Osman Hakan GÜNDÜZ; Emel Ece ÖZCAN-EKŞİ and Esra GİRAY and İlker YAĞCI (Archives of Rheumatology, 2017)
Objectives: Objectives: This study aims to compare ankylosing spondylitis (AS) patients with healthy subjects in terms of posture and balance, and to identify the factors correlated with balance in AS. Patients and methods: Thirty patients (17 males, 13 females; mean age 41.7±7.7 years; range 31 to 57 years) with AS and 33 healthy subjects (18 males, 15 females; mean age 41.3±7.0 years; range 26 to 56 years) were included in the study. Participants were assessed in terms of posture and balance. Posture was assessed using tragus-wall distance, modified Schober’s test, and chest expansion. Balance was assessed using device-assisted balance tests. Pain (visual analog scale) and disease activity (Bath Ankylosing Spondylitis Disease Activity Index) were assessed only in AS patients. Results: Ankylosing spondylitis patients walked more slowly when compared to healthy subjects (p=0.002). As the modified Schober’s test was restricted, AS patients had greater step width in tandem walk and higher sway velocity on foam base (r=-0.418 p=0.022; r=-0.473 p=0.008). Neither Bath Ankylosing Spondylitis Disease Activity Index nor visual analog scale was correlated with balance. Conclusion: Static and dynamic balance are impaired in AS patients when compared to healthy subjects. Restricted mobility of the spine and advanced kyphosis impaired balance, while pain and disease activity had no correlations with balance.